Performing Arts as High-Impact Practice (The Arts in Higher Education, 2018)
This book investigates how the performing arts in higher education nationally contribute to the "high impact practices," as identified by the Association of American Colleges and Universities (AACU). Using the well-known map of the HIPs for illustrating the centrality of performing arts practices in higher education, the editors and authors of this volume call for increased participation by performing arts programs in general education and campus initiatives, with specific case studies as a guide. Performing arts contribute to the efforts of their institution in delivering a strong liberal arts education that uniquely serves students to meet the careers of the future. This is the first book to explicitly link the performing arts to the HIPs, and will result in the implementation of best practices to better meet the educational needs of students. At stake is the viability of performing arts programs to continue to serve students in their pursuit of a liberal arts education.